2014
DOI: 10.1177/0020852314533452
|View full text |Cite
|
Sign up to set email alerts
|

The slow transformation of Swiss federal administrative elites

Abstract: This article sets out to study the profile of Swiss administrative elites at federal level by showing how their profile has evolved in the light of what has come to be known as the wave of New Public Management (NPM), which has benefited from a very fertile ground in Switzerland. These elites correspond to a specific institutional order, in relation to specific organizational structures and workings, and have specific characteristics in terms of career paths and academic background. However, the administrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…3 Similar to inter-ministerial mobility, also inter-sectoral mobility is associated with a broader horizon, human capital acquisition and thus a better preparation for management and leadership tasks in public administration. As part of the NPM movement private sector (management) experience is particularly valued for senior executives, leading to changing competency profiles and to an increase in external recruitments in different parts of the public sector in many countries (e.g., Emery, Giauque, andRebmann 2014, Maor andStevens 1997). There is reason to believe that inter-ministerial mobility as well as inter-sectoral mobility indeed contribute to a higher "employability" of senior officials, based on a cumulative career perspective (Christensen and Laegreid 2009).…”
Section: Managerial Competenciesmentioning
confidence: 99%
“…3 Similar to inter-ministerial mobility, also inter-sectoral mobility is associated with a broader horizon, human capital acquisition and thus a better preparation for management and leadership tasks in public administration. As part of the NPM movement private sector (management) experience is particularly valued for senior executives, leading to changing competency profiles and to an increase in external recruitments in different parts of the public sector in many countries (e.g., Emery, Giauque, andRebmann 2014, Maor andStevens 1997). There is reason to believe that inter-ministerial mobility as well as inter-sectoral mobility indeed contribute to a higher "employability" of senior officials, based on a cumulative career perspective (Christensen and Laegreid 2009).…”
Section: Managerial Competenciesmentioning
confidence: 99%
“…Recent trends in government show that public sector organisations are beginning to follow a similar pattern in transformational change to what was seen in the private sector during the peak of the BPR movement in the 1990s (Yildiz 2007;Currie and Guah 2007;Mahmood et al 2019;Omar et al 2020). Research also shows a significant number of challenges that could impede the implementation process (Iden and Eikebrokk 2015;Hood and Dixon 2015;Hood 2007;Banister and Connolly 2015;Emery et al 2014;Irani et al 2005). Prior studies conducted by Bannister andConnolly (2013, 2015), Choi et al (2011), Jun andWeare, (2010), Fan and Luo (2014), and Omar et al (2020) suggest that when radical change is introduced on the established structure of public institutions, they are pressured to alter their policies and procedures as well as the culture and beliefs of their stakeholders.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we see research on professionals focusing on transformations. Emery et al (2014), for example, investigated changes in the professional profile of Swiss federal administrative elites through indicators such as academic and social capital and career path. Buffat (2014) showed that organizational hybridization affects professionals' professional identities: they also become hybrid.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recently, we see research on professionals focusing on transformations. Emery et al. (2014), for example, investigated changes in the professional profile of Swiss federal administrative elites through indicators such as academic and social capital and career path.…”
Section: Theoretical Frameworkmentioning
confidence: 99%